Sistem Informasi Pelatihan Mobil Pada Citra Indotech Jaya Purwokerto Berbasis Desktop - Yustina Meisella Kristania (Jurnal Khatulistiwa Informatika, 2017)
ABSTRACTIncreasing competition in the business world, making the existence of a computerized data processing is essential in order to assist strategic planning and effective decision making. At the time of this recording customer registration, scheduling training, customer attendance and payment of training at the Training Institute Stir Mobil Indotech Citra Jaya Purwokerto is still done manually so that its performance has not been effective. This is reflected in the determination of fault schedules of participants, attendance and calculation of payment transactions. The goal of this research is the construction of information systems are expected to help improve services and be able to control the process of registration management, payment transactions and allocation process training schedule. Software development method used is the Waterfall. The information system is built using Borland Delphi 7 and MySQL as the database. The end result is an information system training the steering wheel, where interested parties can control the admission of learners, schedules and payment transactions directly without waiting for the statements made by officers to help determine policy-making companies Keywords: Information Systems, Borland Delphi, MySQLProgram Studi Sistem Informasi STMIL Nusa MandiriJl. Salemba Raya No. 5 Jakarta Pusat